Bathing Neonatal in Bimanese Tradition and Its Implication Toward Health - Wulandari, Ade; Haris, Abdul (Universitas Muhammadiyah Semarang, 2018)
Background: Child care practices and parenting are still influenced by some habits that are considered as the basic needs of individuals or groups called cultures. An interesting phenomenon is the practice of newborn care by Bimanese by following tradition that is inherited from generation to generation. These child care practices include self-care hygiene of newborns, known as Kandeu Li, i. Kandeu Li'i is the tradition of bathing the baby for a long time, even the child gets shiver and cyanosis. Objective: to get a description of the tradition of self-care of newborns by Bimanese. Methods: data were obtained through descriptive study conducted in the working area in the Asakota Public Health ServiceÂ of Bima City on 25 families who were taking care of newborns encountered in the research period. Data collection was carried out by interview and observation method. Result: Observation results showed that 80% of respondents soaked the baby more than 10 minutes when the baby was bathed, 84% of the respondents did an additional tradition after the baby was bathed. The results of the interviews revealed that the majority of respondents said they follow the tradition of bathing the baby from inherited tradition and the reason of the respondent soaked the baby and did an additional tradition after bathing is to make baby can sleep more soundly and not easily surprised. Conclusion: Tradition and beliefs of most Bimanese about the newborn's self-care hygiene has high risk and harmful for the health and safety of the baby. Suggestion: As part of a professional health worker, the nurse needs to conduct home visits for families who will have babies to prepare parenting skills.